Ophthalmic effects of petroleum dispersant exposure on common murres (Uria aalge): An experimental study. Issue 1 (15th December 2016) - Fiorello, Christine V.; Freeman, Kate; Elias, Becky A.; Whitmer, Emily; Ziccardi, Michael H.
Abstract: The safety of chemical dispersants used during oil spill responses is largely unknown in birds. We captured common murres in Monterey Bay, CA and exposed them to Corexit EC9500a, crude oil, or a combination in artificial seawater. We performed ophthalmic examinations and measured intraocular pressures and tear production before and after exposure. Loglinear analysis found that exposure to oil or dispersant was related to the development of conjunctivitis and corneal ulcers. Odds ratios for birds exposed to oil or dispersant were positive and significant for the development of conjunctivitis, while odds ratios for the development of corneal ulcers were positive and significant only for birds exposed to a high concentration of oil. Ocular exposure to dispersants and petroleum in seabirds may cause conjunctivitis and may play a role in the development of corneal ulcers. These results have implications for policymakers who develop protocols for the use of dispersants during marine oil spills. Highlights: Chemical dispersants such as COREXIT EC9500a are frequently used during responses to oil spills. Little is known about their safety for seabirds, which are visual predators. We exposed murres to dispersant, oil, or both in artificial seawater to evaluate ocular effects. Dispersants may facilitate the development of lesions in seabird eyes.